2000
DOI: 10.1143/jjap.39.2643
|View full text |Cite
|
Sign up to set email alerts
|

Subtarget Effect on Laser Plasma Generated by Transversely Excited Atmospheric CO2 Laser at Atmospheric Gas Pressure

Abstract: An experimental study has been carried out on the dynamical process taking place in the laser plasma generated by Transversely Excited Atmospheric CO2 laser (100 mJ, 50 ns) irradiation of a soft sample at surrounding helium pressure of 1 atm. It is shown that the presence of a copper subtarget behind the soft sample is crucial in raising the gushing speed of the atoms to the level adequate for the generation of shock wave laser plasma even at atmospheric pressure. It is also found that the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…In this experiment, a brass plate was placed on the backside of the sample in a close contact as a sub-target to enhance the ablation speed. In our previous works, for TEA CO 2 laser bombardment, it was proved that for soft samples, the use of a metal sub-target was essential to overcome the low ablation speed due to the lack of repulsive force [18,[31][32][33]. In fact, in this experiment, fluorine emission cannot be detected when the sub-target was not used even though a crater actually formed on the sample surface.…”
Section: Resultsmentioning
confidence: 92%
“…In this experiment, a brass plate was placed on the backside of the sample in a close contact as a sub-target to enhance the ablation speed. In our previous works, for TEA CO 2 laser bombardment, it was proved that for soft samples, the use of a metal sub-target was essential to overcome the low ablation speed due to the lack of repulsive force [18,[31][32][33]. In fact, in this experiment, fluorine emission cannot be detected when the sub-target was not used even though a crater actually formed on the sample surface.…”
Section: Resultsmentioning
confidence: 92%
“…In other words, LISPS cannot be applied directly to liquid or soft solid samples. [21][22][23] In order to overcome the above problem, we introduced a new technique in which the liquid samples was immediately freezed using a mixture of dry ice and alcohol. It should be noted that the freezing process should be done fast to get a homogeneity in the form of ice sample.…”
Section: Resultsmentioning
confidence: 99%
“…We have nevertheless proved that even for soft sample, shockwave plasma was readily produced when a hard subtarget was placed behind them. [21][22] In order to improve our LISPS technique to liquid sample, recently we have succeeded in applying the laser-induced shockwave plasma spectroscopy (LISPS) for the detection and analysis of metal elements deposited from water sample by means of electrolysis method. It is shown that the elements are generally deposited in the form of thin film on the electrode surface, while the electrode also conveniently serves as a subtarget for the relatively soft metal film, and thereby provides the necessary condition for the generation of shockwave plasma which is favorable for highly sensitive spectrochemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on our experiments, even though the powder was pressed in the form of a pellet, the pellet of powder material is not as hard as the solid sample such as ceramic. Thus, a strong shock wave, which is imperative to produce high-temperature plasma [11][12], cannot be induced because of low repulsion force on the surface of the sample, resulting in weak atomic emission intensity of the plasma. In order to increase the hardness of the powder pellet, material binders like potassium bromide, polyvinyl, starch, aluminum, and silver were employed as reported in this paper [13].…”
Section: ■ Introductionmentioning
confidence: 99%